Evaluating the centralized purchasing policy for the treatment of hepatitis C: The Colombian CASE - Angela V. Pérez; Antonio J. Trujillo; Aurelio E. Mejia; Johnny D. Contreras; Joshua M. Sharfstein (Wiley, 2019)
Abstract The high cost of drugs for hepatitis C limits access and adherence to treatment. In 2017, the Colombian health care system decided to design a strategy. It consisted of centralized purchasing, regulations, clinical practice guidelines, and direct observation of the treatment and follow‐up of patients. The main objective of this study was to assess the centralized purchasing strategy in Colombia. The study design was a policy implementation assessment. We analyzed the change in prices, the clinical outcomes, and the opinions of stakeholders using data from the Ministry of Health. Additional information about effectiveness came from the Colombian Fund for High‐Cost Diseases and semi‐structured interviews of the stakeholders. The follow‐up was from October, 2017 to October, 2018. The total number of patients reported in the cohort period was 1069. The number that finished 12 weeks of treatment, completed the follow‐up for the case closure, and were considered cured through the end of October, 2018 was 563 (53%). The remainder, 506 patients (47%), are currently in treatment. A total of 543 of these treated patients (96%) were cured. After implementing this strategy, the drug prices decreased by more than 90% overall. Before implementation, the total direct cost was $100 102 171.75 dollars. Afterward, the cost was $8 378 747 dollars.